Offering people a choice for colorectal cancer screening. Issue 5 (22nd March 2012) - Senore, Carlo; Ederle, Andrea; Benazzato, Luca; Arrigoni, Arrigo; Silvani, Marco; Fantin, Alberto; Fracchia, Mario; Armaroli, Paola; Segnan, Nereo
Abstract : Objectives: To assess the population coverage and diagnostic yield of offering an immunochemical faecal occult blood test (FIT) to non-responders to a flexible sigmoidoscopy (FS) invitation. Design: A cohort study conducted in a population-based colorectal cancer (CRC) screening programme. In this programme, eligible men and women aged 58 (Turin; 43 748 subjects) or 60 (Verona; 19 970 subjects) are invited, with a personal letter signed by their general practitioner, to undergo an FS. Bowel preparation is limited to a single enema self-administered at home. Subjects in whom one distal polyp >5 mm (≥10 mm in Turin) or at least one adenoma (one advanced adenoma or more than two adenomas in Turin) is detected at FS are referred for colonoscopy. People who do not respond to the invitation to undergo an FS are invited to have an FIT (OC-Sensor; Eiken, Tokyo, Japan; single sample, cut-off 100 ng/ml). Attendance rate and neoplasia yield were analysed in four consecutive birth cohorts. Results: Overall participation rate for the FS invitation was 39.3% in Verona and 29.9% in Turin. Of the eligible non-responders to the FS invitation, 19.3% (95% CI 18.9% to 19.7%) underwent an FIT. As a result, the proportion of people undergoing screening by FS or FIT was 55.2% in Verona and 39.3% in Turin, with no gender differences in either centre. FIT detected 8.3% of all advanced adenomas and 20.4% of all CRCs diagnosed at screening. Conclusions: A strategy involving the sequential offer of FS and FIT is a feasible and efficient approach. FIT in people not attending for FS increases screening uptake and detection of advanced adenomas and CRCs.